An Investigation on the Migration and Settlement Law of Temporary Plugging Particles in Horizontal Wellbore. (29th November 2021) - Luo, Yao; Lang, Hao; Yang, Dan; Wen, Xianli; Guo, Jianshe; Kong, Hui; Meng, Xue; Han, Shaobo; Zhou, Fujian
Abstract : Migration and settlement of temporary plugging particles of different sizes affect the effect of temporary plugging, which in turn affect the effect of reservoir reconstruction. However, the migration and settlement laws of temporary plugging particles in horizontal wellbore are still unclear. In order to study the migration and settlement laws of temporary plugging particles in horizontal wellbore, a set of multicluster perforation physical model experiment device for horizontal wells was built. Based on this experimental device, the effects of mass ratio, pumping rate, and adding sequence on the migration and settlement laws of temporary plugging particles were studied, respectively. The experimental results show that the 3 mm temporary plugging particles move forward in a leaping manner at the bottom of the horizontal wellbore and the 1 mm particles are distributed in layers in the horizontal wellbore, and the particles are less in the upper part of the wellbore and more in the bottom of the wellbore. The migration trajectory of the two mixed particles is similar to the single. Under different mass ratio, the settlement mass of particles in the perforation clusters at the outlet end is greater than that in the entrance end. When the 3 mm particles account for a relatively large amount (m 3 mm : m 1 mm = 5 : 1 ), the settlement mass of the particles in the two perforation clusters is greater than other mass ratio conditions. For the same perforation, the settlement mass becomes greater as the proportion of 3 mm increases. When only 3 mm particles are considered, with the increasing of displacement, the mass of particles in the perforation clusters at the inlet end increases, and the mass of particles in the clusters at the outlet end decreases. With the increase of displacement, the sedimentation mass of particles in high angle perforations decreases, while the sedimentation mass in other perforations increases. Adding 3 mm first and then 1 mm particles, the particle settlement mass in the perforation cluster at the outlet end is twice the mass of the particles in the perforation cluster at the inlet end. Reversing the sequence, the settlement masses of the particles in the two clusters are almost equal. The particle distribution in the perforation at different angles has obvious gradation. The smaller the angle, the greater the settlement mass of the temporary plugging particles. This research results will provide reference for temporary plugging and fracturing construction.